2010
DOI: 10.1051/0004-6361/200912462
|View full text |Cite
|
Sign up to set email alerts
|

New results on thermal and photodesorption of CO ice using the novel InterStellar Astrochemistry Chamber (ISAC)

Abstract: Aims. We present the novel InterStellar Astrochemistry Chamber (ISAC), designed for studying solids (ice mantles, organics, and silicates) in interstellar and circumstellar environments: characterizing their physico-chemical properties and monitoring their evolution as caused by (i) vacuum-UV irradiation; (ii) cosmic ray irradiation; and (iii) thermal processing. Experimental study of thermal and photodesorption of the CO ice reported here simulates the freeze-out and desorption of CO on grains, providing new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(60 citation statements)
references
References 31 publications
7
53
0
Order By: Relevance
“…On the other hand, microwave discharge lamps have a significantly higher flux; however, independent measurements of CO photodesorption have shown that the derived yield is dependent on having a well-calibrated lamp spectrum. Muñoz Caro et al (2010) determined a desorption yield for pure CO ice of (3.5 ± 0.5 × 10 −2 ) photon −1 which is one order of magnitude higher than that from Öberg et al (2009a). Recent investigations showed that the FUV spectrum, in particular the ratio of Lyman-α (121.6 nm) to H 2 molecular emission bands (110-180 nm), is sensitive to the gas pressure, the type of lamp, the gas composition (pure H 2 versus a mixture of H 2 and He) and the window properties (Chen et al 2014;Ligterink et al 2015).…”
Section: Experimental Studiesmentioning
confidence: 62%
“…On the other hand, microwave discharge lamps have a significantly higher flux; however, independent measurements of CO photodesorption have shown that the derived yield is dependent on having a well-calibrated lamp spectrum. Muñoz Caro et al (2010) determined a desorption yield for pure CO ice of (3.5 ± 0.5 × 10 −2 ) photon −1 which is one order of magnitude higher than that from Öberg et al (2009a). Recent investigations showed that the FUV spectrum, in particular the ratio of Lyman-α (121.6 nm) to H 2 molecular emission bands (110-180 nm), is sensitive to the gas pressure, the type of lamp, the gas composition (pure H 2 versus a mixture of H 2 and He) and the window properties (Chen et al 2014;Ligterink et al 2015).…”
Section: Experimental Studiesmentioning
confidence: 62%
“…To help understand how it can be possible to observe those molecules in the gas phase in many lines of sight, the effect of irradiation on ices has been studied. Muñoz-Caro et al (2010) demonstrate that if the effect of UV photons (induced by cosmic rays) on CO ices is taken into account, an equilibrium between solid and gas phase is reached, because of ice desorption from dust produced by secondary photon irradiation. But this is not the only interaction producing desorption of icy components.…”
Section: Discussion and Astrophysical Implicationsmentioning
confidence: 87%
“…Seperuelo perform a series of experiments where the desorption rate induced by H, Ni and Fe ions are estimated, concluding that the effect of heavy ions is even more important than the effect of protons in the ISM. The works performed by Muñoz-Caro et al (2010) andSeperuelo Duarte et al (2010), are relevant for the ISM because, even though CO can be mixed with water ice, from the absorption profile studied by Ehrenfreund et al (1996), it is possible to deduce that CO could be embedded in a nearly separate ice phase.…”
Section: Discussion and Astrophysical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations